Blockchain for Marketing Transparency and Trust: Applications in Supply Chain and Customer Loyalty Programs - Fachri Afif; Perengki Susanto (Penerbit Jurnal Indonesia, 2025)
Blockchain for Marketing Transparency and Trust: Applications in Supply Chain and Customer Loyalty Programs. The increasing demand for transparency and trust in marketing practices necessitates innovative solutions. This paper explores the potential of blockchain technology to enhance transparency and build trust in two critical marketing areas: supply chain management and customer loyalty programs. By providing a decentralized, immutable, and auditable ledger, blockchain can offer unprecedented visibility into product origins, ethical sourcing, and the secure management of loyalty rewards. 1 This study examines the theoretical underpinnings of blockchain and analyzes potential applications and benefits for both businesses and consumers. Specifically, it investigates how blockchain can improve supply chain transparency by tracking product journeys from origin to consumer, and how it can revolutionize customer loyalty programs by ensuring secure and transparent reward distribution and redemption. Furthermore, the paper discusses the challenges and opportunities associated with implementing blockchain in these marketing contexts. Ultimately, this research argues that blockchain technology holds significant promise for fostering greater transparency and trust, leading to stronger brand-consumer relationships and more ethical marketing practices.